A autonomia médica em debate: análise de discurso do conselho federal de medicina e do médicos pela vida sobre as disputas de poder sobre o uso do tratamento precoce na pandemia de Covid-19 - Crestani, Verônica Bonotto (2024)
This research deals with the Coronavirus pandemic that began in March 2020 and the search for establishing an effective treatment to combat Covid-19. In Brazil, there was a clash between scientific discourse and political discourse, leading doctors and medical entities to position themselves in ambiguous and distinct ways. The government initially maintained confidence in Chloroquine, a medicine cited by other national leaders, such as Trump. Throughout the pandemic, chloroquine, along with other medicines, comprised early treatment, which was proposed not only as a treatment for Covid-19, but as an immunizer, which would prevent the disease. The present research intends to investigate early treatment through the application of the Covid-Kit, with the promise of curing and preventing the disease, initially, without scientific corroboration of its effectiveness, and later, without corroborated effectiveness. The objective of this work is to map medical discourses about the ‘Covid-Kit’, or ‘early treatment’ from the beginning of the pandemic to the beginning of the vaccination period. We analyzed how the enunciative modalities regarding the effectiveness of using the Covid-Kit in the treatment of Covid-19 are constituted for its defenders. The theoretical-methodological contribution used to think about the processes that are intertwined in the formation of the discourses that defend the Covid-Kit, was established based on the concepts presented by Michel Foucault and applied in the methodological form of discourse analysis by Fairclough (2001). Thus, an archaeogenealogy, based on Foucauldian theory, is proposed as a theory that structures the methodology, which allows thinking about a set of assumptions about reality, and offers a conceptual instrument that will give meaning to the qualitative treatment of data and which aims to think how beliefs were produced throughout the pandemic. We want to understand how the concepts used in the discursive formation on the use of early treatment were adjusted, and how the enunciative modalities that oppose scientific knowledge to medical power were formed. Therefore, the research problem deals with how the relationship between medical knowledge-power and the knowledge-power represented by the scientific consensus regarding the use of chloroquine and the covid-kit occurs during the Covid-19 pandemic in Brazil?